2023
DOI: 10.1126/scisignal.add3269
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental disorder–associated mutations in TAOK1 reveal its function as a plasma membrane remodeling kinase

Abstract: Mutations in TAOK1 , which encodes a serine-threonine kinase, are associated with both autism spectrum disorder (ASD) and neurodevelopmental delay (NDD). Here, we investigated the molecular function of this evolutionarily conserved kinase and the mechanisms through which TAOK1 mutations may lead to neuropathology. We found that TAOK1 was abundant in neurons in the mammalian brain and remodeled the neuronal plasma membrane through direct association with phosphoin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…The finding cortical migration defects such as of PVNH is highly consistent with the cellular and developmental role of TAOK1 in neuronal migration, as defined by previous functional studies both in vitro and in animal models [ 4 , 11 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding cortical migration defects such as of PVNH is highly consistent with the cellular and developmental role of TAOK1 in neuronal migration, as defined by previous functional studies both in vitro and in animal models [ 4 , 11 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although large–scale WES and array-CGH studies had already identified TAOK1 as a candidate gene for NDDs since 2011 [ 9 , 10 ], the direct association has been confirmed only recently [ 11 , 12 ]. Some of these studies clearly documented that defects in TAOK1 expression can affect neuronal maturation and cortical development both in vitro and in animal models [ 4 , 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together, the mitochondrial related genes with granulosa/oocyte Cellular Component enrichment (mitochondrial pathways and high energetic dependent pathways egg: spindle) converged to the idea that this non competent oocyte and associated cells in follicle are molecularly delayed, as previously stated, and mature oocytes have low mitochondrial activity (Beeman et al, 2023). Still, in the oocyte, we may find pathways that support our ideas, such as DNA replication, TGF-Beta, and nucleocytoplasmic transport.…”
Section: Discussionsupporting
confidence: 82%
“…Reinforcing this, we found the gene TAOK1 (TAO kinase 1) as a DEG, and at the same time methylated in the BL group suggesting that his expression occurred possible during or before maturation and must be repressed at the end of oocyte maturation. This gene triggers microtubules instability and disassembly in neuronal studies (Beeman et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This membrane sculpting function might be conserved, as among the forty-seven human Ste20 kinases, SLK and LOK, the two human orthologues of Slik, as well as Tao1 and Tao3, are predicted to feature a C-terminus with the three bundled alpha-helices characteristic of Slik. Recently, Tao1 was shown to promote the growth of neuron dendritic arbor (Beeman et al, 2023). There was speculation that Tao1 could remodel membranes through its potential BAR domain, although this was not experimentally tested.…”
Section: Discussionmentioning
confidence: 99%